Thin Slices of Athletes’ Nonverbal Behavior Give Away Game Location: Testing the Territoriality Hypothesis of the Home Game Advantage - Furley, Philip; Schweizer, Geoffrey; Memmert, Daniel (Evolutionary psychology, 2018)
The present research investigated whether perceivers could detect who is playing at home or away in soccer matches based on thin slices of professional (Experiment 1) and amateur (Experiment 3) athletes’ nonverbal behavior prior to the match and whether perceivers rated athletes playing at home relatively higher on behavioral dimensions (Experiments 2 and 3) linked to territoriality. In Experiment 1 (N = 80), participants watched short videos depicting soccer players prior to a UEFA Champions League match and rated whether athletes were more likely to be playing at home or away. In Experiment 2 (two groups N = 102 and N = 101), perceivers rated these videos in terms of assertiveness, dominance, and aggression. In Experiment 3, we replicated the procedure of Experiments 1 and 2 with different stimulus material from amateur soccer (N = 112). Participants could significantly differentiate between home playing and away playing athletes (Experiment 1: d = 0.44 and Experiment 3: d = 1.07). Experiments 2 and 3 showed that perceivers rated professional and amateur soccer players higher on assertiveness (d = 0.34-0.63), dominance (d = 0.20-0.55), and aggression (d = 0.16-0.49) when playing at home compared to playing away. Findings are supportive of evolutionary accounts of nonverbal behavior, ecological approaches to person perception, and the thin slices of behavior hypothesis by demonstrating that humans change their nonverbal behavior depending on game location. We discuss the relevance of the present findings for the home advantage in sports.
Gesehen am 31.07.2019